Antibacterial compounds from the root of the indigenous Australian medicinal plant Carissa lanceolata R.Br. - Hettiarachchi, Dhanushka; Locher, Cornelia; Longmore, Robert (Taylor & Francis, 2011)
The conkerberry, Carissa lanceolata R.Br. (Apocynaceae), is commonly used by many indigenous Australian communities across Northern Australia for the treatment of a variety of conditions such as chest pain, toothache, colds and flu. Indigenous uses of this plant strongly argue for an antibacterial bioactivity. The aim is to identify antibacterial compounds from root material of C. lanceolata, therefore confirming the indigenous use of the plant. Antibacterial activity was examined against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Bacillus subtilis using a micro broth dilution technique. Three compounds demonstrating considerable activity were isolated. The volatile phenolic compound 2′-hydroxyacetophenone and the lignan carinol both were reported for the first time from C. lanceolata, whereas this is the second account of the occurrence of carissone. All three compounds showed activity, with 2′-hydroxyacetophenone and carinol having a minimum inhibitory concentration of <1.25 mg mL−1 against all four bacteria. Extracts and compounds isolated from C. lanceolata roots were found to possess a significant antibacterial activity, confirming the indigenous use of this plant.